Therapeutic yoga for spiritual well-being and life skills: Yogis’ perception in Nepal and Thailand - Ashton , Ann Suwaree (Nepalese Culture, 2026)
This paper examines how yoga practice enhances spiritual well-being and life skills. With growing interest in non-pharmacological approaches to maintaining health, especially amid environmental changed and pandemics investigating yoga’s role in holistic health is timely. A qualitative design used in-depth interviews with twenty-one professional trained yoga practitioners in  Nepal and Thailand. Participants included yogis and instructors from Asian and Western backgrounds who attended yoga session and school while travelling in Thailand and Nepal. Findings indicate that yoga promotes personal spiritual well-being and can be function as a traditional therapeutic tool that supports life-skill development. Core benefits linked to enhanced spiritual well-being include heightened self-awareness, sustained stillness, focused attention, moral sensitivity, detachment from materialism, a sense of sacredness and connectedness, and felt closeness to God in whom they have faith. Improvements in life skill that follow include emotional regulation, clearer decision making, conflict resolution, social empathy, resilient coping. This study offers theoretical and practical contributions regarding how authentic traditional yoga practice foster spiritual well-being and leads to physical and supports psychological health.